Acute pancreatitis and type 2 diabetes mellitus: who is guilty? - Kucukler, Ferit; Simsek, Yasin; Baglicaklioglu, Murat; Adali, Gupse; Guler, Serdar (The European Research Journal, 2015)
Many factors play a role in the etiology of acute pancreatitis and its pathogenesis is not fully understood. Dipeptidyl peptidase 4 (DPP-4) inhibitors are a new group of agents for the treatment of Diabetes Mellitus (DM). There are some controversies about specific adverse events such as pancreatitis and hypersensitivity reactions. A 50-year-old morbid obese woman presented with upper abdomen pain after the eating food, nausea and vomiting. She was diagnosed with type 2 diabetes mellitus 7 years ago. Vildagliptin had been added to her treatment six months ago. Abdominal examination revealed epigastric tenderness with guarding. Laboratory data revealed elevated pancreatic enzymes. Abdominal computed tomography (CT) showed features of pancreatitis. Vildagliptin was stopped and patient’s symptoms had diminished in parallel with normalization of pancreatic enzymes; and at the 5th day patient was discharged with healthy condition. She was free of symptoms and all laboratory data were normal at the 30th day after discharge. It is important to keep in mind that diabetic patients have an increased risk of pancreatitis which may be related to obesity, hyperlipidemia and/or drugs.